1993
DOI: 10.1002/star.19930450403
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Quercus leucotrichophora (Oak) Starch

Abstract: Starch from the seeds of Quercus leucotrichophora was isolated, purified and its physico‐chemical properties were determined. Scanning electron microscopy of the granules show that they are oval to eliptical in shape. Its has high contents of ash, lipids, proteins and lower content of amylose. Its gelatinization temperature is 80–85°C and displays high water binding capacity. It has low swelling power but high solubility. Amylograph study shows 425 B.U. paste viscosity and no thinning inspite of 3 h heating. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 8 publications
(3 reference statements)
8
40
1
Order By: Relevance
“…Riley et al [30] reported that solubility increased with decreasing amylose content. The observation for the noodles is similar with the result obtained from of Soni et al [37] who associated high solubility with high amylose content. The difference could be attributed to differences in granule sizes and their arrangement within their cells.…”
Section: Cooking Properties Of Trifoliate Yam-wheat Noodlessupporting
confidence: 91%
“…Riley et al [30] reported that solubility increased with decreasing amylose content. The observation for the noodles is similar with the result obtained from of Soni et al [37] who associated high solubility with high amylose content. The difference could be attributed to differences in granule sizes and their arrangement within their cells.…”
Section: Cooking Properties Of Trifoliate Yam-wheat Noodlessupporting
confidence: 91%
“…Also, the mean S of all the samples under study had significant differences among them, with GS (12.40%) recording the highest whilst RF (9.47%) recorded the least. The highest S recorded by the GS in this study is attributed to the easy solubility of the linear fraction (amylose) which leach out during swelling process since it is loosely linked with the rest of the macro molecular structure (Soni et al, 1993;Adebowale et al, 2014). The results obtained for SP and S were in the same range of the values reported by Qazi et al, 2014.…”
Section: Color Measurementsupporting
confidence: 85%
“…The moisture contents of both starches are within the 10 to 20% moisture level recommended for commercial starches (Soni et al, 1993). The ash contents of cassava (0.29%) and cocoyam (0.09%) are low, and within the limit 0.5% recommended for grade A industrial starches (Radley, 1976).…”
Section: Physicochemical Propertiesmentioning
confidence: 70%